2011
DOI: 10.1212/wnl.0b013e31820db341
|View full text |Cite
|
Sign up to set email alerts
|

Clinical immunology of the sphingosine 1-phosphate receptor modulator fingolimod (FTY720) in multiple sclerosis

Abstract: The oral sphingosine 1-phosphate (S1P) receptor (S1PR) modulator fingolimod has been shown to be effective in the treatment of patients with relapsing multiple sclerosis (MS). The drug binds with high affinity to 4 of the 5 G-protein-coupled S1P receptors (S1P(1-5)). After binding, the receptors are internalized, degraded, and thus functionally antagonized by fingolimod. Under physiologic conditions, S1P(1) mediates the egress of lymphocytes from secondary lymphoid organs to the peripheral circulation. Functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
104
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(111 citation statements)
references
References 66 publications
6
104
0
1
Order By: Relevance
“…The S1P receptor modulator FTY720 (Gilenya) has been approved as frontline treatment for relapsing/remitting multiple sclerosis (8,9). FTY720 is phosphorylated in vivo by sphingosine kinase 2 to form the active metabolite FTY720 phosphate (FTY720P), which is a high affinity agonist of all the endothelial differentiation gene family S1P receptors except S1P 2 (10 -12).…”
mentioning
confidence: 99%
“…The S1P receptor modulator FTY720 (Gilenya) has been approved as frontline treatment for relapsing/remitting multiple sclerosis (8,9). FTY720 is phosphorylated in vivo by sphingosine kinase 2 to form the active metabolite FTY720 phosphate (FTY720P), which is a high affinity agonist of all the endothelial differentiation gene family S1P receptors except S1P 2 (10 -12).…”
mentioning
confidence: 99%
“…Because low plasma HDL-cholesterol is associated with a predominance of proinflammatory phenotype of monocyte-derived macrophage [48], these findings suggest an immunosuppressive role of HDL in the development of MS lesions. This interpretation is further supported by the beneficial therapeutical effects of fingolimod in the disease [49].…”
Section: Pathophysiological Mechanismsmentioning
confidence: 69%
“…SP1 receptors are widespread in CNS cells and a defect of sphingolipid and phospholipid metabolism is observed early in normal appearing white and grey matter in MS patients. Moreover, S1P is reduced in affected white matter and is increased in CSF of these patients [49]. Importantly, FTY720 treatment has been shown to have neuroprotective effects independent of immunomodulatory mechanisms [50].…”
Section: Pathophysiological Mechanismsmentioning
confidence: 99%
“…4 (c)). Mehling et al 25) reported that the reductions in circulating T lymphocytes are predominantly in naïve T cells and central memory T cells (TCM) subsets. This may be related to the fact that naïve T cells and TCM express high levels of CCR7.…”
Section: Discussionmentioning
confidence: 99%